2008
DOI: 10.1291/hypres.31.1835
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Treatment with Valsartan Improved Cyclic Variation of the Myocardial Integral Backscatter Signal and Diastolic Dysfunction in Hypertensive Patients: The Echocardiographic Assessment

Abstract: Myocardial fibrosis is the major determinant of diastolic property of the left ventricle (LV).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…As these integrated backscatter measures have been shown to reflect structural changes of the fibrous components of the myocardium, these findings suggest attenuation of myocardial fibrosis by losartan, but not by amlodipine. The losartan-induced reduction in myocardial fibrosis is an agreement with previous studies using biopsied tissues [11] and resembles the findings obtained using the same non-invasive technique in another recent study with valsartan [24].…”
Section: Discussionsupporting
confidence: 91%
“…As these integrated backscatter measures have been shown to reflect structural changes of the fibrous components of the myocardium, these findings suggest attenuation of myocardial fibrosis by losartan, but not by amlodipine. The losartan-induced reduction in myocardial fibrosis is an agreement with previous studies using biopsied tissues [11] and resembles the findings obtained using the same non-invasive technique in another recent study with valsartan [24].…”
Section: Discussionsupporting
confidence: 91%
“…Regression of ultrasonic myocardial texture alterations have been already documented in clinical scenarios of hypertrophy regression [26,27]. Although our results showed a trend toward regression of both IBS indices (CC IBS and CV) after treatment of patients with overt hypothyroidism or hyperthyroidism, this was only statistical significant in CV of hypothyroidism patients.…”
Section: Discussionsupporting
confidence: 43%
“…As a blocker in Ang II receptor, the potential effects of valsartan have been widely investigated in the diseases of different organs, including liver fibrosis , kidney injury and cardiovascular injury, especially heart failure and cardiac hypertrophy . It has been found that treatment with valsartan could significantly inhibit the TGF‐β pathway and further attenuate the progression of liver fibrosis of the liver .…”
Section: Introductionmentioning
confidence: 99%